2000
DOI: 10.1128/aac.44.12.3257-3263.2000
|View full text |Cite
|
Sign up to set email alerts
|

Candidacidal Activities of Human Lactoferrin Peptides Derived from the N Terminus

Abstract: In light of the need for new antifungal agents, the candidacidal activities of human lactoferrin (hLF) and synthetic peptides representing the first, hLF(1-11), and second, hLF(21-31), cationic domains of its N terminus were compared. The results revealed that hLF(1-11) was more effective in killing fluconazole-resistant Candida albicans than hLF(21-31) and much more effective than lactoferrin, as determined microbiologically and by propidium iodide (PI) staining. By using hLF(1-11) and various derivatives, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(110 citation statements)
references
References 43 publications
2
107
1
Order By: Relevance
“…The maximum hyphal damage by the various antimicrobial peptides amounted to 70-80%, which was similar to the values for ≥0.1 nM amphotericin B. Comparison of the EC 50 values for the various peptides revealed that dhvar5 (EC 50 = 3±1 μM) is the most potent peptide; the EC 50 values for hLF (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), hLF(21-31), dhvar4, UBI 18-35, and UBI 29-41 being 29±5 μM, 142±13 μM, 19±5 μM, 37±15 μM, and 91±19 μM, respectively. Notably, hLF(1-11) is 5-fold more effective than hLF(21-31), dhvar5 is 6-fold more potent than dhvar4, and UBI 18-35 is almost 3-fold more effective than UBI 29-41 in damaging A. fumigatus hyphae.…”
Section: Antifungal Activities Of Antimicrobial Peptidesmentioning
confidence: 48%
See 4 more Smart Citations
“…The maximum hyphal damage by the various antimicrobial peptides amounted to 70-80%, which was similar to the values for ≥0.1 nM amphotericin B. Comparison of the EC 50 values for the various peptides revealed that dhvar5 (EC 50 = 3±1 μM) is the most potent peptide; the EC 50 values for hLF (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11), hLF(21-31), dhvar4, UBI 18-35, and UBI 29-41 being 29±5 μM, 142±13 μM, 19±5 μM, 37±15 μM, and 91±19 μM, respectively. Notably, hLF(1-11) is 5-fold more effective than hLF(21-31), dhvar5 is 6-fold more potent than dhvar4, and UBI 18-35 is almost 3-fold more effective than UBI 29-41 in damaging A. fumigatus hyphae.…”
Section: Antifungal Activities Of Antimicrobial Peptidesmentioning
confidence: 48%
“…The results revealed a dose-dependent antifungal activity against A. fumigatus hyphae for hLF (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) (Fig. 1).…”
Section: Antifungal Activities Of Antimicrobial Peptidesmentioning
confidence: 99%
See 3 more Smart Citations